Current and Future Perspectives on the Role of Probiotics, Prebiotics, and Synbiotics in Controlling Pathogenic Cronobacter Spp. in Infants - Ke, Alfred; Parreira, Valeria R.; Goodridge, Lawrence; Farber, Jeffrey M. (Frontiers in Microbiology, 2021)
Cronobacter species, in particular C. sakazakii, is an opportunistic bacterial pathogen implicated in the development of potentially debilitating illnesses in infants (<12 months old). The combination of a poorly developed immune system and gut microbiota put infants at a higher risk of infection compared to other age groups. Probiotics and prebiotics are incorporated in powdered infant formula and, in addition to strengthening gut physiology and stimulating the growth of commensal gut microbiota, have proven antimicrobial capabilities. Postbiotics in the cell-free supernatant of a microbial culture are derived from probiotics and can also exert health benefits. Synbiotics, a mixture of probiotics and prebiotics, may provide further advantages as probiotics and gut commensals degrade prebiotics into short-chain fatty acids that can provide benefits to the host. Cell-culture and animal models have been widely used to study foodborne pathogens, but sophisticated gut models have been recently developed to better mimic the gut conditions, thus giving a more accurate representation of how various treatments can affect the survival and pathogenicity of foodborne pathogens. This review aims to summarize the current understanding on the connection between Cronobacter infections and infants, as well as highlight the potential efficacy of probiotics, prebiotics and synbiotics in reducing invasive Cronobacter infections during early infancy.